Clinical applications of non-culture based methods for the diagnosis and management of opportunistic and endemic mycoses - Verweij, P. E.; Figueroa, J.; Van Burik, J.; Holdom, M. D.; Dei-Cas, E.; Gomez, B. L.; Mendes-Giannini, Maria José Soares [UNESP] (B I O S Scientific Publishers Ltd, 2000)
Nonculture based methods for the detection of infections caused by fungal pathogens are becoming more important tools in the management of infected patients. Detection of fungal antigens and DNA appear to be the most promising in this respect for both opportunistic and endemic mycoses. In this article we present an overview of the most recent developments in nonculture based methods and examine their value in clinical practice.
Keywords: antigenemia; molecular analyses; nonculture diagnosis; PCR diagnosis